Cerebrospinal Fluid Total Tau Protein Correlates With Longitudinal, Progressing Cognitive Dysfunction in Anti-Neural Autoantibody-Associated Dementia and Alzheimer’s Dementia: A Case–Control Study - Hansen, Niels; Juhl, Aaron Levin; Grenzer, Insa Maria; Hirschel, Sina; Teegen, Bianca; Fitzner, Dirk; Bartels, Claudia; Timäus, Charles; Wiltfang, Jens; Malchow, Berend (Frontiers in Immunology, 2022)
Background Neural autoantibody-associated dementia (NABD) is an increasing phenomenon in memory clinics with a high impact on later therapy. Biomarkers are lacking that differentiate this type of dementia from neurodegenerative dementia such as Alzheimer’s dementia (AD). Our aim is to analyze neurodegeneration markers and their relationship to progressing cognitive dysfunction in NABD and AD to test for tools differentiating these two forms of dementia prior to neural autoantibody testing. Methods In our retrospective, observational study, we investigated 14 patients with dementia and serum and/or cerebrospinal fluid (CSF) neural autoantibodies as well as 14 patients with AD by relying on recent CSF and clinical criteria for AD. Patient files were checked for psychopathology, neuropsychological test performance, autoimmune indicators, CSF, and MRI results. Results Our patient groups did not differ in their psychopathology, autoimmune indicators, or MRI profile. The progression of cognitive dysfunction [as measured by the difference in Mini-Mental State Examination (MMSE) scores since disease onset, and the yearly progression rate (MMSE loss/per year)] did not vary significantly between groups. Total tau protein was significantly higher in AD patients than NABD patients revealing no signs of Alzheimer’s disease pathology in their CSF (p < 0.05). Total tau protein levels in CSF correlated with cognitive decline since disease onset (r = 0.38, p < 0.05) and yearly progression rates (r = 0.56, p < 0.005) in all patients. Discussion Our results suggest that the progression of cognitive dysfunction as defined by MMSE does not seem to be an appropriate biomarker for distinguishing NABD from AD. However, the total tau protein level in CSF might be a relevant molecular biomarker that can indicate disease pathology and/or progression in both known AD and NABD, which is often accompanied by axonal degeneration. Total tau protein may be an additional diagnostic tool with which to differentiate anti-neural-associated dementia from AD if further research confirms these proof-of-concept findings in larger patient cohorts.